Citric Acid Modified Bentonite for Congo Red Adsorption - Zhang, Hanbing; Zhou, Juan; Muhammad, Yaseen; Tang, Rui; Liu, Kun; Zhu, Ying; Tong, Zhangfa (Frontiers in Materials, 2019)
Raw bentonite (RB) was chemically modified by citric acid (CA) to obtain a low-cost and environment-friendly citric acid incorporated bentonite (CAB) adsorbent, which was applied for the adsorptive removal of Congo Red (CR). The effect of adsorbent dosage, contact time, ionic strength, surfactant, and pH on adsorption was investigated. Adsorption equilibrium data fitted well with Langmuir model while the Langmuir adsorption capacity of CR on CAB reached up to 384 mg·g−1. Furthermore, CR adsorption on CAB followed pseudo-second kinetic model while intra-particle diffusion was not the only rate-limiting step as determined from intra-particle diffusion model investigation. RB and CAB were characterized by XRD, FT-IR, and BET techniques. A proposed mechanism for the adsorption of CR over CAB suggested the chemical adsorption phenomenon is mainly controlled by chelation, hydrogen bonding, and fixing.